(untitled) (Dhaka University Journal of Science, 2016)
Mobile ad hoc network is a temporary wireless network consisting of mobile nodes. Frequent route breakage is a common event in Every node is equipped with battery energy. This form of energy is one of the scarce resources in MANET. This paper is focused on promiscuous mode to observe packets coming from the nodes within a direct transmission range. At the same time critical energy of a routing node is used to find the low energy node on an ongoing route. This low energy node will perform local route repairing scheme such as QLR-APM to find alternate node of low energy node which avoids route breakage in MANET. This approach prevents route breakage and the same time packet loss and retransmission of packets are reduced in MANET. Thus it is easily seen that QLR-APM incorporating this proposed approach outperforms than QLR-APM. Dhaka Univ. J. Sci. 64(1): 39-44, 2016 (January)